Peruvian Chemistry Olympiad 2016-2017: the path to success - Ortega-San-Martín, Luis (2017)
The years 2016 and 2017 have allowed consolidating the position and importance of the Peruvian Chemistry Olympiad as an activity that encourages the study of chemistry and the desire to improve in today's students. Although 2016 ended with good results at the international level, the successes achieved in 2017 have overshadowed them: one gold and one bronze medals in the IChO 2017 and one gold and three silver medals in the OIAQ. Nationally, the Peruvian Chemistry Olympiad (OPQ) has maintained the high level of enrollment and in 2017 we have again exceeded two thousand participants.